Compatibility of Transactional and Interpersonal Conversation Texts in MTs English Textbook With The Standard of Content - Nuha, Ulin (Jurnal Penelitian, 2019)
In this study, I analyzed the transactional and interpersonal conversation texts found in grade VIII English textbook entitled “EOS English on Sky 2”. This textbook is still much used at SMP or MTs although it was published a couple years ago. I also analyzed the linguistic features of the transactional and interpersonal conversations in the English textbook. It is assumed by the writers of the English textbook that the transactional and interpersonal conversation texts found in the English textbook are compatible with the standard of content as mentioned in curriculum 2006, School-based Curriculum (KTSP or Kurikulum Tingkat Satuan Pendidikan). The standard of content in KTSP 2006 develops student’s linguistic competence in people’s experience, ideas, and feelings and understands various meanings.This study focuses on the issues of structural-functional approach which analyzes the speech function, structural approach which analyzes linguistic features,This is a qualitative study. In calculating the data and the final result of data percentage, quantification was used to support this study. The data are transactional and interpersonal conversation texts written in grade VIII English textbook. Units of analysis in this study are moves and clauses. The conversation texts are presented in 8 units. The moves were analyzed functionally and the clauses were analyzed structurally.The result shows that the speech functions of the transactional conversation texts are 54.5% matching the standard of content, the speech functions of the interpersonal conversation texts are 2.1% matching the standard of content, the linguistic feature applied in the transactional and interpersonal conversation texts uses the linguistic feature in functional literacy level, the speech functions of conversation texts introduced in EOS English on Sky 2 for MTs grade VIII are less compatible with the standard of content based on the compatibility levels.